2005
DOI: 10.1007/s10681-005-1644-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on vegetative, reproductive and qualitative traits of seven diploid and tetraploid watermelon lines

Abstract: Seven tetraploid watermelon lines developed by colchicine treatments were compared with their diploid counterpart for plant, flower, fruit, seed and qualitative characteristics. Tetraploid genotypes attained statistically higher vine thickness (8.04 mm), leaf area (298.9 cm 2 ) and chlorophyll content (55.6) while internode length and chlorophyll fluorescence was similar to their corresponding diploid. Both pistillate and staminate flower organs (pedicel, anther, ovary, stigma, petals) were larger in tetraploi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 25 publications
5
44
0
2
Order By: Relevance
“…Additionally, the tetraploids flowered in lower percentages. Similar delays in flowering time of a few days were Data of the nuclear DNA content represent mean ± SD of three samples each with two replications noted in autotetraploids of Zizyphus jujube (Gu et al 2005) and Gerbera jamesonii (Gantait et al 2011) and delays of 2 and 3 weeks in Citrullus lanatus (Jaskani et al 2005) and Vicia villosa (Elradi and Unal 2010), respectively. Our observations showed that initial growth of tetraploids was very slow, but during the next season tetraploids were significantly larger than diploids.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Additionally, the tetraploids flowered in lower percentages. Similar delays in flowering time of a few days were Data of the nuclear DNA content represent mean ± SD of three samples each with two replications noted in autotetraploids of Zizyphus jujube (Gu et al 2005) and Gerbera jamesonii (Gantait et al 2011) and delays of 2 and 3 weeks in Citrullus lanatus (Jaskani et al 2005) and Vicia villosa (Elradi and Unal 2010), respectively. Our observations showed that initial growth of tetraploids was very slow, but during the next season tetraploids were significantly larger than diploids.…”
Section: Discussionsupporting
confidence: 52%
“…We also found that the chlorophyll content was higher in daylily tetraploids compared to diploids. This increase in chlorophyll content has been often observed e.g., in neotetraploids of Vicia villosa (Elradi and Unal 2010), mango (González-Rodríguez and Grajal-Martín 2013), and watermelon (Jaskani et al 2005). In general, tetraploidisation resulted in positive trends in enhancement of cells, stomata, organs, plant vigor, and/or biomass.…”
Section: Discussionmentioning
confidence: 59%
“…Those leaf characters changed were also found by Omidbaigi et al, (2010) in basil (non-orchid). Jaskani et al, (2005) observed gigantic form of tetraploid watermelon leaf with higher leaf area index than diploid counterparts. Torres et al, (2011) discovered tomatillo polyploid showed higher plant height and fruit weight and diameter.…”
Section: Seedling Growth and Developmentmentioning
confidence: 83%
“…In the recent time, a polyploidy program had developed by Chen et al, (2011b) in Taiwan, to convert over 20 diploid Phalaenopsis species to tetraploid, in order to fill up the needs of the industry. Polyploidy also very important and have been improved various crops characteristics: watermelon (Jaskani et al, (2005), Phlox (Zhang et al, (2008), tomatillo (Torres et al, (2011)), etc. Polyploidy can increase genetic variability and improve flower characteristics, therefore floriculture is probably the most benefited from this technique (Griesbach, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Citrullus lanatus L. Matsumura & Nakai is one of the most important of them with respect to cultivation area, production and commercial transactions volume. This species is monoecious and naturally crosspollinated (Jaskani et al, 2005;Ellul et al, 2007) with outcrossing rate arounding 75% (Ferreira et al, 2008). There is a need of urgent conservation program to avoid a serious depletion of the genetic richness of oilseed C. lanatus.…”
Section: Introductionmentioning
confidence: 99%